Overcoming Heparin-Associated RT-qPCR Inhibition and Normalization Issues for microRNA Quantification in Patients with Acute Myocardial Infarction - Coelho-Lima, Jose; Mohammed, Ashfaq; Cormack, Suzanne; Jones, Samuel; Das, Rajiv; Egred, Mohaned; Panahi, Pedram; Ali, Simi; Spyridopoulos, Ioakim (Thrombosis and Haemostasis, 2018)
Background Cardiac-enriched micro ribonucleic acids (miRNAs) are released into the circulation following ST-elevation myocardial infarction (STEMI). Lack of standardized approaches for reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) data normalization and presence of RT-qPCR inhibitors (e.g. heparin) in patient blood samples have prevented reproducible miRNA quantification in this cohort and subsequent translation of these biomarkers to clinical practice.Materials and Methods Using a RT-qPCR miRNA screening platform, we identified and validated an endogenous circulating miRNA as a normalization control. In addition, we assessed the effects of in vivo and in vitro anticoagulant drugs administration (heparin and bivalirudin) on three RT-qPCR normalization strategies (global miRNA mean, exogenous spike-in control [cel-miR-39] and endogenous miRNA control). Finally, we evaluated the effect of heparin and its in vitro inhibition with heparinase on the quantification of cardiac-enriched miRNAs in STEMI patients.Results miR-425–5p was validated as an endogenous miRNA control. Heparin administration in vitro and in vivo inhibited all RT-qPCR normalization strategies. In contrast, bivalirudin had no effects on cel-miR-39 or miR-425–5p quantification. In vitro RNA sample treatment with 0.3 U of heparinase overcame heparin-induced over-estimation of cardiac-enriched miRNA levels and improved their correlation with high-sensitivity troponin T.Conclusion miRNA quantification in STEMI patients receiving heparin is jeopardized by its effect on all RT-qPCR normalization approaches. Use of samples from bivalirudin-treated patients or in vitro treatment of heparin-contaminated samples with heparinase are suitable alternatives for miRNA quantification in this cohort. Finally, we reinforce the evidence that cardiac-enriched miRNAs early after myocardial reperfusion reflect the severity of cardiac injury.
Keywords: microRNA; RT-qPCR normalization; heparin; bivalirudin; myocardial infarction